Impact of Self-Energy Recycling and Cooperative Jamming on SWIPT-Based FD Relay Networks with Secrecy Constraints - Silva, Isabella Wanderley Gomes Da [UNESP]; Sanchez, Jose David Vega; Olivo, Edgar Eduardo Benitez [UNESP]; Moya Osorio, Diana Pamela (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This paper investigates the secrecy performance of a power splitting-based simultaneous wireless information and power transfer cooperative relay network in the presence of an eavesdropper. The relay is considered to operate in full-duplex (FD) mode to perform both energy harvesting and information decoding simultaneously. To accomplish that, the relay is assumed to employ two rechargeable batteries, which switch between power supplying mode and charging mode at each transmission block. We also assume that the self-interference inherent of the FD mode is not completely suppressed. Therefore, it is assumed that, after some stages of passive and active self-interference cancellation, there is still a residual self-interference (RSI). A portion of this RSI (remaining after passive cancellation) is recycled for energy harvesting. In order to improve the system secrecy performance, it is considered that the relay can split its transmit power to send the information signal and to emit a jamming signal to degrade the eavesdropper's channel. The secrecy performance is evaluated in terms of the secrecy outage probability and the optimal secrecy throughput. Tight-approximate and asymptotic expressions are obtained for the secrecy outage probability, and the particle swarm optimization method is employed for addressing the secrecy throughput optimization problem. From numerical results, we show that the secrecy performance can be increased depending on the self-energy recycling channel condition. Finally, our derived expressions are validated via Monte Carlo simulations.
Keywords: Cooperative jamming; full-duplex; physical layer security; relaying; simultaneous wireless information and power transfer